Increasing knowledge of health and psychology for migrant workers - Anni Fithriyatul Mas'udah; Laily Isro’in; Dianita Rifqia Putri (Universitas Muhammadiyah Magelang, 2023)
The workload of Indonesian migrant workers (PMI) has a significant impact on both physical and psychological health. One consequential issue is the prevalence of chronic kidney failure (CKD) among PMI in Ponorogo who undergo hemodialysis (HD). PMI often remain unaware of whether their behaviors in migrant countries contribute to CKD. This community service initiative aims to educate PMI about behaviors that pose a risk of causing CKD. The service activities unfold in three stages. The first stage involves a presentation on psychology, followed by an explanation regarding health, and concluding with a discussion. The outcome of this initiative is an increase in knowledge among prospective PMIs regarding both health and psychology. Knowledge about CKD increased by 30%, motivation saw a 14% increase, social support rose by 34%, and there was a 39% increase in support for a healthy living environment. These findings suggest that prospective PMIs can better prepare themselves for work in migrant countries by prioritizing attention to both physical and psychological health, even amidst lifestyle differences.